A comparison between Right Unilateral Ultrabrief electroconvulsive therapy and bilateral electroconvulsive therapy in the elderly: a pilot naturalistic observational study. (August 2018) - Narchal, Shalini; Harris, Anthony WF; Allen, Bruce
Objectives: To compare clinical outcomes and adverse effects between Bitemporal (BT) and Right Unilateral Ultrabrief (RUL(UB)) electroconvulsive therapy (ECT) in an elderly population. Methods: Patients over the age of 65 years admitted to a tertiary referral hospital over a seven month period requiring ECT received RUL(UB) ECT. They were compared with those who received BT ECT over these and the preceding seven months. Results: Twenty-three patients entered the study. No significant differences was observed between the groups in demographic and clinical characteristics or clinical improvement. However, patients who received BT ECT were significantly more likely to be confused post treatment compared with the RUL(UB) group. Conclusions: This pilot study found RUL(UB) ECT to be an effective treatment in elderly patients. These patients also suffered significantly less confusion than patients who received BT ECT.